1998
DOI: 10.1016/s0741-5214(98)70015-1
|View full text |Cite
|
Sign up to set email alerts
|

The differential effect of contrast agents on endothelial cell and smooth muscle cell growth in vitro

Abstract: This study demonstrates that brief exposure to contrast agents injures EC and SMC, altering their structure and decreasing proliferation for up to 7 days in vitro. This response is both dose and time dependent. EC are more severely affected by ionic contrast, and SMC are more severely affected by nonionic contrast. EC injury appears to be mediated by the osmolar effect of the contrast, but the effects of contrast on SMC seem to be due to a different mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Previous work reported that brief, high-concentration CM exposure causes injury to endothelial cells and retards their subsequent growth[10,2931]. In the present study, we demonstrate that prolonged exposure to clinically relevant, low concentrations of CM inhibits the proliferation of endothelial cells.…”
Section: Discussionsupporting
confidence: 73%
“…Previous work reported that brief, high-concentration CM exposure causes injury to endothelial cells and retards their subsequent growth[10,2931]. In the present study, we demonstrate that prolonged exposure to clinically relevant, low concentrations of CM inhibits the proliferation of endothelial cells.…”
Section: Discussionsupporting
confidence: 73%
“…However, prior studies suggest that sodium ions, as opposed to osmolality, are the more likely cause. 22,23 Increasing the physiologic sodium ion concentration by 25% reduced vascular SMC numbers by almost 50%. 22 While the chloride concentration also is increased by the addition of NaCl, it too appears unlikely to decrease the number of SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…1-3). VSMCs as well as endothelial cells exhibit diminished viability or proliferation in a dose-and time-dependent manner after exposure to CMs in vitro (12,25,31). Intravascular injection of CMs seems to cause adverse effects on the blood vessel, which is composed of endothelial cells and VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is less nephrotoxicity with iso-osmolar CMs than with low-osmolar CMs (1). CMs are cytotoxic to the proliferation and the function of endothelial cells and vascular smooth muscle cells (VSMCs) (25,26). Exposure of endothelial cells to CMs induces apoptotic cell death (23) and alters the adhesion of neutrophils (33).…”
mentioning
confidence: 99%